A case study of regional warehousing at Integrated Warehouse Sdn. Bhd. (IWS) Port Klang / Azmady Abdul Aziz - Abdul Aziz, Azmady (1992)
Integrated Warehouse Sdn. Bhd.. (IWS) was set up to undertake the entire warehousing division of Integrated Forwarding and Shipping Sdn. Bhd.(IFS) and operate the largest network of Public Bonded Warehouses in Malaysia. IWS give services for imported cargoes and Free Trade Zone. IWS is trying to improve their services especially in their warehouse operation. This is to make sure that they can reduce time and cost of warehouse operation as well as to maximise the profit through space utilisation.